Economies of reputation: the case of revenge porn. Issue 2 (3rd April 2017) - Langlois, Ganaele; Slane, Andrea
ABSTRACT: Revenge porn involves publicly releasing pictures of a person's sexual activity, along with the means to contact that person, to provoke widespread shaming. This paper analyzes the US-based revenge porn website MyEx.com through discourse, legal, and information network analyses. The paper explores how revenge porn is not only an instance of online sexual violence rooted in abjection but also symptomatic of a new political economy of subjectivity, where both the human-based and the automated, algorithm-based circulation of personal information are at the center of processes through which the self is seen and valued, both socially and economically, by others.